The Birman–Hilden property of covering spaces of nonorientable surfaces - Atalan, F.; Medetogullari, E. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.5Let $p: \widetilde{N} → N$ be a finite covering space of nonorientable surfaces, where $χ(\widetilde{N}) < 0$. We search whether or not $p$ has the Birman–Hilden property.